Student and Perceived Instructor Big Five Traits as Predictors of Rapport and Course Grades - Anna E. Park; J. Arthur Gillaspy, Jr.; William Lammers (International Journal for the Scholarship of Teaching and Learning)
Studies show that student-instructor rapport is correlated with student success in college courses (e.g., Lammers & Gillaspy, 2013). Less is known about the personality traits of students and their perceptions of instructors’ personality traits that are associated with rapport. This study addressed this gap in the literature. In an online survey, students self-reported their big five personality traits. They then thought about a particular class from the previous semester. They rated the associated instructor’s big five and their rapport with the instructor. Their ratings of their instructor’s big five were more predictive of rapport than their own self-reported big five. Perceived instructor agreeableness and openness were the strongest predictors of rapport. Rapport fully mediated the relationship between instructor agreeableness and course grade. Perceived instructor agreeableness and openness may help students feel a sense of rapport with their instructors. Rapport, in turn, may help students be successful in the course.